Post-kommunistisk kulturomvandling - Lennhag, Mi (Budkavlen, 2023)
Recension av: Törnquist-Plewa, Barbara & Stala, Krzysztof (eds.) 2011. Cultural Transformations after Communism. Central and Eastern Europe in Focus. Nordic Academic Press, Lund. 336 s. ISBN 978-91-85509-59-1.